One-transistor one-resistor (1T1R) cell for large-area electronics - Ghenzi, Néstor (2018)
We developed a one-transistor one-resistor cell composed of one TiO2-based resistive switching (RS) device and one ZnO-based thin-film transistor (TFT). We study the electric characteristics of each component individually, and their interplay when both work together. We explored the direct control of bipolar RS devices, using our TFTs to drive current in both directions. We also report striking power implications when we swap the terminals of the RS device. The target of our work is the introduction of RS devices in large-area electronic (LAE) circuits. In this context, RS devices can be beneficial regarding functionality and energy consumption, when compared to other ways to introduce memory cells in LAE circuits.